Kajian Budaya Dalam Keberagaman Pada Komunikasi Antarabudaya Pada Siswa SMA MARDI YUANA KOTA SUKABUMI - Rahayu, Hilda Sri; Jaya, Umban Adi; Wijaya, Zeffanya Radhael; Gunawan, Ce; Hamdalah, Farhan (LPPM Universitas HKBP Nommensen, 2024)
This study aims to explore the impact of intercultural communication related to multiculturalism, cultural differences, and language as a cultural map at SMA Mardi Yuana, Sukabumi City, Indonesia, on efforts to build national unity. The author used qualitative research methods with semi-structured interview techniques, through a case study approach from the participants. The results of the interviews were thematically analyzed by the author and then grouped based on the similarity of views expressed by the informants. The author found that there are significant differences in students' opinions regarding tolerance and multiculturalism based on gender. Male student informants tend to have a higher tendency to have a negative opinion on problems caused by differences in ethnicity, religion and race compared to female students. Gender plays a role in students' perceptions of social and cultural issues. These findings highlight the importance of education on tolerance and inclusion in schools. By understanding the complexity of students' views and the factors that have an impact on them, schools and educational institutions can design more effective programs in promoting tolerance, respect and inclusion among students, thus forming a generation that is more empathetic, inclusive and appreciative of multiculturalism.